Investasi Emas sebagai Instrumen Lindung Nilai Syariah di Tengah Ketidakstabilan Ekonomi: Studi Kasus pada Pengguna Aplikasi TRING - Diana Purnamasari (Jurnal Perbankan Syariah, 2025)
This study aims to understand the experiences of TRING app users in investing in gold as a sharia-compliant hedging instrument amid economic instability. The study uses a qualitative approach that allows researchers to explore the meanings, motivations, and perceptions behind digital gold investment decisions. Data was collected through in-depth interviews with users of various age groups and analyzed by identifying indicators that emerged during the interview process.The results show that gold is viewed as a stable, safe asset that complies with sharia principles, making it the primary choice for preserving wealth. The TRING application is perceived as providing easy access, fast transactions, and features that make it easy for novice investors to invest in gold without having to purchase physical gold. Trust and security proved to be the dominant factors influencing user loyalty, including guarantees of gold authenticity, price transparency, data protection, and compliance with sharia principles. In addition, digital gold investment provides psychological peace of mind for users, especially when facing unstable economic conditions.